Sour Apples - Connolly, Sheila (Connolly, Sheila. Orchard mystery., 2012)
Apple orchard owner Meg Corey is finally feeling settled into her new life in Granford - she's made friends, and her relationship with Seth Chapin is heating up - when her old Boston coworker Lauren Converse comes barreling into town, running the congressional campaign for a former hometown football hero. But Meg doesn't have time to worry about Lauren's campaign, because her neighbor, outspoken dairy farmer Joyce Truesdell, is found dead. Was the outspoken dairy farmer really kicked in the head by one of her cows?